2015
DOI: 10.3892/ijmm.2015.2418
|View full text |Cite
|
Sign up to set email alerts
|

Crocin protects retinal ganglion cells against H2O2-induced damage through the mitochondrial pathway and activation of NF-κB

Abstract: Glaucoma is a degenerative nerve disorder that results in irreversible blindness. It has been reported that the apoptosis of retinal ganglion cells (RGCs) is a hallmark of glaucoma. Oxidative stress is one of the major factors that cause apoptosis of RGCs. Crocin has many beneficial effects, including antioxidant and anti-apoptotic actions. However, the mechanism by which crocin protects against oxidative stress‑induced damage to RGCs remains unclear. The present study aimed to investigate the mechanism by whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 44 publications
2
23
0
1
Order By: Relevance
“…Saffron and its active ingredients mainly crocin, crocetin and safranal exert anti-proliferative, anti-tumor, anti-inflammatory, anti-oxidant, anti-apoptotic, and hepatoprotective effects [12] . Administration of saffron components in different models of retinal damage and degeneration showed neuroprotective effects [13] , [14] . Likewise, safranal could slow down photoreceptor degeneration in the P23H rat model of retinitis pigmentosa, reflected by improved a- and b-wave amplitudes in electroretinographic recordings and a preserved vascular network [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Saffron and its active ingredients mainly crocin, crocetin and safranal exert anti-proliferative, anti-tumor, anti-inflammatory, anti-oxidant, anti-apoptotic, and hepatoprotective effects [12] . Administration of saffron components in different models of retinal damage and degeneration showed neuroprotective effects [13] , [14] . Likewise, safranal could slow down photoreceptor degeneration in the P23H rat model of retinitis pigmentosa, reflected by improved a- and b-wave amplitudes in electroretinographic recordings and a preserved vascular network [14] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown previously that crocin exhibits multiple activities, including anti-cancer, anti-inflammatory and anti-oxidation effects in various cell types ( 7 ). Lv et al ( 8 ) reported that crocin exerts an anti-oxidative effect against H 2 O 2 -induced apoptosis in retinal ganglion cells.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial stress leads to the release of cell death mediators, which compromise oxidative phosphorylation, leading to inefficient use of protons and the relative over- and underproduction of ROS and adenosine triphosphate (ATP) respectively [ 28 , 40 ]. The associated increase in ROS may be involved in the propagation of RGC apoptosis via mediation of mitochondrial permeability transition, alteration of mitochondrial membrane potential, and release of pro-apoptotic proteins [ 28 , 41 ]. SkQ1, mentioned previously, has been shown to prevent mitochondrial damage in fibroblasts in the presence of oxidative stress and stimulate formation of the mitochondrial network in the absence of oxidative stress by reducing endogenous ROS levels [ 42 ].…”
Section: Formation Of Reactive Oxygen Species Resulting From Diseamentioning
confidence: 99%
“…The administration of tempol, which has been shown to prevent ROS generation and neuronal cell death, increases survival of RGCs exposed to tumor necrosis factor-alpha (TNF-α) and hypoxia in the presence of a caspase inhibitor [ 28 ]. Furthermore, crocin, a carotenoid, has been shown to suppress production of ROS, increase mitochondrial membrane potential, and enhance viability in hydrogen peroxide (H 2 O 2 )-insulted RGCs [ 41 ]. Molecular hydrogen has also been demonstrated to suppress loss of mitochondrial membrane potential and apoptosis in retinal cells, presumably via peroxynitrite scavenging [ 34 ].…”
Section: Formation Of Reactive Oxygen Species Resulting From Diseamentioning
confidence: 99%